2023
DOI: 10.47352/bioactivities.2963-654x.182
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Several Types of Weed Extracts on The Growth of Escherichia coli

Abstract: Escherichia coli is a type of Gram-negative bacteria that is commonly found in the human digestive tract. It has been reported as one of the bacteria that has been resistant to several antibiotics. This study aims to determine four (4) types of weed extracts that are considered but have not been used as antibacterial compounds against E. coli. This experimental study used a completely randomized design with several types of plant extracts, namely Acalypha indica L., Ageratum conyzoides, Phyllanthus niruri L., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Elif Ayşe Erdoğan Eliuz has also investigated the antibacterial properties of citric acid against E. coli, S. aureus, and C. albicans as a sanitizer agent [70]. Moreover, Song et al have reported the antibacterial effects of salicylic acid [21]. However, this is the first time reporting the synergistic antibacterial activity of all these antioxidants.…”
Section: Evaluation Of Antibacterial Activity Of Antioxidants Interca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Elif Ayşe Erdoğan Eliuz has also investigated the antibacterial properties of citric acid against E. coli, S. aureus, and C. albicans as a sanitizer agent [70]. Moreover, Song et al have reported the antibacterial effects of salicylic acid [21]. However, this is the first time reporting the synergistic antibacterial activity of all these antioxidants.…”
Section: Evaluation Of Antibacterial Activity Of Antioxidants Interca...mentioning
confidence: 99%
“…The quest for natural and secure antimicrobial compounds that can regulate pathogenic bacteria like Escherichia coli and Staphylococcus aureus in the food sector has been spurred by the increased need for security when handling food [18][19][20][21]. There is substantial evidence that the antioxidant, antibacterial, and antiinflammatory effects of natural Organic Acids (OAs).…”
Section: Introductionmentioning
confidence: 99%